PM.82 Acute Hyponatraemia in Labour – The Obstetric Marathon?. (26th April 2013) - Sokhal, P; Cook, J; Robinson, S; Lakasing, L
Abstract : Maternal hyponatraemia during labour can affect both mother and baby. As a result, standard intrapartum care includes administration of oxytocin in sodium-containing fluids, limitation of oral intake and use of isotonic sports drinks. There is no strict guidance on best practise and local protocols vary. We present a case report of acute severe hyponatraemia following spontaneous vaginal delivery at 38 +5 weeks gestation in a 34-year-old primiparous woman. This previously well woman spent 4.5 hours in the birthing pool and drank approximately 6 litres of water/lucozade in that time. After delivery, she suffered a seizure and acute confusion. The plasma sodium was 117 mmol/L (135–145 mmol/l). This was corrected with hypertonic saline to 130 mol/L within 4 hours. She was admitted to intensive care and required sedation and ventilation. Endocrine investigations revealed no underlying cause. Differential diagnoses included atypical eclampsia and posterior-reversible encephalopathy syndrome. She was discharged on day 6 with a Mini-mental State Examination score of 30/30. Isotonic drinks prevent urinary ketosis, maintain plasma glucose and electrolytes, thereby preventing the 'starvation effect' of labour, also seen in marathon runners. Review of the literature relating to the effect of water immersion and oral fluid intake on plasma sodium levels during labour suggests that a 40-minute bath may cause increased naturiesis and plasma volume expansion. Water tolerance appears diminished in labour and thus intoxication may be possible with relatively moderate volumes. We recommend that in labour a) women do not drink excessively, b) hypotonic fluid administration is avoided, c) fluid-balance charts become mandatory.